TEKNIK KOMUNIKASI DAKWAH GURU DALAM MENANAMKAN NILAI IMAN DAN AKHLAK KEPADA PESERTA DIDIK TK LPQ ADAM HAWA LIMBUNG KEC.BAJENG KAB. GOWA : penelitian deskriptif - nasywaa haniyah; Hj.nur laelah; ratika nengsi; Hj.nur setiawati; muhammad syahrul (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to explore and understand the Islamic Preaching communication techniques applied by teachers in instilling the values of faith and morality in students at Qur’anic Educational Instutions Adam Hawa Limbung, Bajeng District, Gowa Regency. This research employs a qualitative approach with a phenomenological method. Data were collected through observation, in-depth interviews, and documentation. The findings reveal that teachers use various Islamic Preaching communication techniques suited to the characteristics of early childhood, including exemplary behavior, repetition, Islamic storytelling, persuasive communication, and an affectionate approach. Teachers also habituate students to practice moral values in daily life, such as greeting, asking for permission, maintaining cleanliness, and helping others. These techniques convey religious messages not only verbally but also through emotional engagement and real-life practices, making the values easier to understand and internalize. In conclusion, the Islamic preaching communication techniques implemented at Qur’anic Educational Instutions Adam Hawa have proven effective in shaping students into individuals who are faithful and morally upright from an early age.